تأثير اضطراب طبقة الغلاف الجوي السطحية في ارتفاع تنصيب العنفة الريحية - أبو حامد, فريد; مسوح, فواز; عامر, ردينة (Latakia University Journal -Engineering Sciences Series, 2016)
The aim of this paper is to investigate the overlap between lower atmospheric boundary layer and real wind turbine wake which installed not far from ground surface, Here we adopted rotating actuator-disk model (RADM) as a complex model of 3D actuator-disk model, virtual blade modeling (VBM) and tip loss correction, in order to get more reliability and satisfied result.Wind turbines have grown significantly in size over the last years and, it generally placed in an atmospheric boundary layer, then the assumption of uniform wind velocity cannot be valid. The lower part of atmospheric boundary layer has a high level of turbulence intensity and great velocity gradients, then when wind turbine placed in these conditions, a high rate of fluctuation will occur subsequently power losses in wind farms, and change wake turbulence character which affects the flow-induced dynamic loads on downwind turbines.يهدف هذا البحث إلى اكتشاف التمازج الحاصل بين اضطراب طبقة الغلاف الجوي السفلى والجريان خلف عنفة ريحية بإبعاد حقيقية على ارتفاع مناسب عن سطح الأرض، اعتمدت الدراسة نموذج القرص الفعال في الحالة الدورانية (RADM) كنموذج مختلط بين حالة القرص الفعال ثلاثي البعد 3D ، ونموذج الريشة الافتراضي VBM، وتم إدخال تصحيح ضياعات طرف الريشة TLC وذلك من اجل تقريب النموذج من الحالة الواقعية.في الجزء السفلي من طبقة الغلاف الجوي السطحية ترتفع نسبة الاضطراب نتيجة عدة عوامل ، وتتدرج السرعة مع الارتفاع الشاقولي عن الأرض، ومع ازدياد أحجام العنفات الريحية مؤخراً و وازدياد قطر الدوار و بنتيجة وقوعها ضمن الجزء المضطرب من طبقة الغلاف الجوي أصبح لايمكن عد توزع السرعة منتظما على كامل الدوار.إن تدرج السرعة على ارتفاع الدوار ونسبة الاضطراب المرتفعة في الجزء السفلي منه يؤدي إلى زيادة أحمال التعب على الريش وامتداد اضطراب اعقاب الجريان الى مسافات اكبر مما يزيد من الضياعات في المزرعة الريحية ويقلل من الطاقة السنوية المنتجة AEP.